2014
DOI: 10.1097/wno.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Comparison of OnabotulinumtoxinA (Botox) and IncobotulinumtoxinA (Xeomin) in the Treatment of Benign Essential Blepharospasm

Abstract: No difference between Xeomin and Botox was detected in either subjective or objective measures for the treatment of BEB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…No differences were found with multiple measures over 5 treatment sessions. 10 Commonly reported adverse events (AEs) with BoNT injections included periorbital hematoma (25%), ptosis (range of risk differences [RDs] 13%-54%), dry eyes (range of RDs 7.1%-13%), and blurred vision (RD 42%).…”
mentioning
confidence: 99%
“…No differences were found with multiple measures over 5 treatment sessions. 10 Commonly reported adverse events (AEs) with BoNT injections included periorbital hematoma (25%), ptosis (range of risk differences [RDs] 13%-54%), dry eyes (range of RDs 7.1%-13%), and blurred vision (RD 42%).…”
mentioning
confidence: 99%
“…Another direct comparison of incobotulinumtoxinA and onabotulinumtoxinA was made in a prospective, randomized, double-blind, split-face trial in 48 patients who had previously received onabotulinumtoxinA treatment for blepharospasm ( Table 1 ). 32 Patients received four injections of each formulation to either side of the face, using the same number of dose units for incobotulinumtoxinA and onabotulinumtoxinA. No significant difference was found between incobotulinumtoxinA and onabotulinumtoxinA in the changes from baseline in BSDI scores ( P =0.8161) or JRS scores ( P =0.2314).…”
Section: Clinical Efficacy and Safetymentioning
confidence: 93%
“…All these data are summarized in the recent AAN guidelines . A direct comparison of onabotulinumtoxinA and incobotulinumtoxinA in the treatment of benign essential blepharospasm, performed using a split-face technique, showed no differences between the two products in either subjective or objective measures (Saad and Gourdeau, 2014). More recently, results of a TRUDOSE pilot study suggested that onabotulinumtoxinA and incobotulinumtoxinA for cervical dystonia and blepharospasm are not equivalent and do not support the 1:1 dose ratio.…”
Section: Pharmacological Safetymentioning
confidence: 99%